(untitled) (MAUSAM, 1978)
In this paper, some results are given which help support the idea that the tropical disturbances propagating over the Indian Ocean during the northern summer, are an important phenomenon of the broad-scale Indian monsoon. Time-longitude sections of cloudiness over the Indian Ocean during one month and a half of the 1975 summer monsoon stress the existence of moving disturbances: eastward-moving ones in the northern Indian Ocean and westward-moving ones in the southern Indian Ocean. These perturbations as well as their zonal propagation are also evidenced at ground level. From a comparative analysis with balloon trajectories, it is shown that they can have an influence on the low-level air flow circulation over the Indian Ocean. The intensity of the Mascarene High Pressure, located near 3OGS, 5OGE, is studied in relation with the occurrence of the westward-moving disturbances. It is shown that these disturbances modulate the anticyclone intensity of the broad-scale monsoon system with a q\1asi-biweekly period. The relationship found by Findlater (1969) between the low-level cross-equatorial winds over Kenya and rainfall over the western coast of India is investigated with focus on the tropical disturbances propagating eastwards over the northern Indian Ocean. An increase of the intensity of the Somalia jet Occurs each time a perturbation originates over the western Arabian Sea and begins moving eastwards. The rainfall mechanism over the south part of the western coast seems to be linked to these perturbations and rainfall maxima occur a few days before the pressure minima. The relationship, with a 3-4 day lag between wind maxima over Kenya and rainfall maxima over the western coast can be well explained with the eastward-moving tropical disturbances